2009
DOI: 10.1590/s1519-69842009000100025
|View full text |Cite
|
Sign up to set email alerts
|

Proteocephalid cestode infection in alien fish, Cichla piquiti Kullander and Ferreira, 2006 (Osteichthyes: Cichlidae), from Volta Grande reservoir, Minas Gerais, Brazil

Abstract: This work evaluates the variation of the parasitological indexes in 114 Cichla piquiti Kullander and Ferreira, 2006 (tucunaré) infected by two proteocephalid species (Cestoda) for the period of August 1999 to June 2001 in the Volta Grande reservoir, MG, Brazil. The relation between the parasitosis with rainfall and water quality (pH, electric conductivity, oxygen, chlorophyll, transparency and temperature) is discussed. Prevalence of Proteocephalus macrophallus (Diesing, 1850) and/or P. microscopicus (Woodla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
21
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(23 citation statements)
references
References 40 publications
2
21
0
Order By: Relevance
“…These studies can indicate the fish food habit, as has been reported by Machado et al (1996), Takemoto et al (2004Takemoto et al ( , 2009 and Martins et al (2009). Piscivorous fish occupy the top of the food web and may present more chance of infection (Machado et al, 1996;Martins et al, 2009), while omnivorous fish present lower risks of infection by the fact that they are primary consumers in the food web (Feltran et al, 2004;Takemoto et al (2009).…”
Section: Introductionmentioning
confidence: 77%
See 4 more Smart Citations
“…These studies can indicate the fish food habit, as has been reported by Machado et al (1996), Takemoto et al (2004Takemoto et al ( , 2009 and Martins et al (2009). Piscivorous fish occupy the top of the food web and may present more chance of infection (Machado et al, 1996;Martins et al, 2009), while omnivorous fish present lower risks of infection by the fact that they are primary consumers in the food web (Feltran et al, 2004;Takemoto et al (2009).…”
Section: Introductionmentioning
confidence: 77%
“…Martins et al (2009) noticed that moderate infection rates by proteocephalidean cestodes have been registered in fish from several parts of the world, since this endohelminthes is distributed uniformly in several aquatic habitats . In that opportunity, Martins et al (2009) found high parasite load by Proteocephalus macrophallus (Diesing, 1850) Scholz, Chambrier, Prouza andRoyero 1996 andP. microscopicus Woodland, 1935 in Cichla piquiti Kullander and Ferreira, 2006 from the Volta Grande Reservoir, MG, Brazil.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations